ANALISIS KONSUMSI MASYARAKAT DI INDONESIA - Parsaulian, Baginda; Aimon, Hasdi; Anis, Ali (Program Studi Magister Ilmu Ekonomi, 2013)
ABSTRACT The purpose of this study to identify and analyze: (1) consumption of the previous period, the current period disposable income and disposable income previous period on the level of consumption in Indonesia (2) the current period disposable income, disposable income of the previous period, the consumption of the current period, consumption and interest rates on saving the current period in Indonesia (3) inflation and money supply current period the interest rate in Indonesia (4) income taxes in the current period against Indonesia. The results showed (1) there is a significant effect between the consumption of the previous period, disposable income of the current period and disposable income together the level of consumption in Indonesia. (2) There is a significant effect between the current period disposable income, disposable income of the previous period, the current period consumption, the consumption of the previous period and current period interest together towards savings in Indonesia. (3) There is significant inflation period between now and the money supply current period jointly against interest rate in Indonesia. (4) There is a significant effect between the current period income tax in Indonesia. Keywords Consumption, Disposable Income, Interest Rates, Saving, Money Supply, Income Taxes and Inflation